Pengaruh Sumber Daya Manusia, Sistem Informasi Akuntansi, Dan Teknologi Informasi Terhadap Kecenderungan Kecurangan Akuntansi - Elvin Bastian; Sely Indah Nurfaliani (Universitas Serang Raya, 2023)
The Research to how human resources, accounting information systems, and information technology affect the tendency of accounting fraud. Type research is quantitative, and the data used are primary data sourced from questionnaires distributed to manufacturing companies in Cilegon City according to the sample criteria using proposive sampling. The sample research is middle management and low management manufacturing companies located. Of the 120 questionnaires distributed, only 54 were processed. the data analyzed with IBM SPSS software version 23. The results obtained are Human Resources, Accounting Information Systems, and Information Technology partially have a positive and significant effect on the tendency of accounting fraud.